1981
DOI: 10.1182/blood.v57.3.452.452
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cell proliferation and cell migration in the Sezary syndrome

Abstract: The patterns of cell proliferation and cell migration were studied in three patients with the Sezary syndrome using autoradiographic techniques. Cell labeling patterns following pulse labeling with tritiated thymidine in vivo indicated that Sezary cells proliferate actively in skin and in lymph nodes but that few if any Sezary cells proliferate in the peripheral blood. In two of the patients serial samples were obtained. Label dilution patterns in skin and blood over time suggested that circulating Sezary cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As AURKA expression is linked to mitosis and therefore its upregulation might be only owing to accelerated cell proliferation of cell lines as compared with nonproliferating primary T cells, we also compared the expression of primary, circulating tumor cells in SS patients with those in healthy controls. Of note, SS cells do not considerably proliferate in the blood compartment (Bunn et al, 1981). As shown in Figure 2, the tumor cells of approximately half of the patients showed distinct upregulation of AURKA when compared with the healthy controls.…”
Section: Aurka Expression Is Upregulated In Ctcl Tumor Cells As Well As In Ctcl Cell Linesmentioning
confidence: 88%
“…As AURKA expression is linked to mitosis and therefore its upregulation might be only owing to accelerated cell proliferation of cell lines as compared with nonproliferating primary T cells, we also compared the expression of primary, circulating tumor cells in SS patients with those in healthy controls. Of note, SS cells do not considerably proliferate in the blood compartment (Bunn et al, 1981). As shown in Figure 2, the tumor cells of approximately half of the patients showed distinct upregulation of AURKA when compared with the healthy controls.…”
Section: Aurka Expression Is Upregulated In Ctcl Tumor Cells As Well As In Ctcl Cell Linesmentioning
confidence: 88%
“…Previous studies have described SS cells as quiescent and apoptotic-resistant malignant lymphocytes classifying SS principally as an accumulative disorder [15, 41]. Although earlier studies using tritiated thymidine labeling in vivo generically indicated a higher SS cells proliferation in skin and lymph nodes [42] here we demonstrated, with more accuracy, to what extent the skin-resident SS cells proliferate more respect to those of blood using the Ki67 analysis, a widely recognized marker of cell activation/proliferation in daily pathologic practice [43]. We also observed that skin PI increases with the expansion of tumor burden measured as blood TCR-VÎČ clonality indicating that skin and blood compartments are interconnected, thus supporting the concept that activation/proliferation plus apoptosis resistance could determine the SS clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These tumor-derived Tregs then prevent the induction of effective antitumor immunity by inhibiting cytotoxicity by CD8+ T cells (Piccirillo and Shevach, 2001). This allows the malignant CD4+ T cells to persist in the skin and migrate into the lymph nodes and peripheral blood (Bunn et al ., 1981). Subsequently, with increasing tumor burden, additional changes develop such as decreased TCR complexity in the normal T cells and reduced tumor IL-2 responsiveness.…”
Section: Discussionmentioning
confidence: 99%